Accessibility in the Smart City - Trieste, Giuseppe; Gabrielli, Silvia (TeMA - Journal of Land Use, Mobility and Environment, 2014)
FIABA is a cultural route for all, its aim is to promote a Global Accessibility and a Universal Usability through the removal of architectural, cultural, psychological and sensory barriers. FIABA is carrying out a real change and a cultural renewal in the name of equal opportunities. Respect for the environment in which we live is also a duty towards the younger generations to whom we must deliver a world in which free movement and the normal use of spaces are goals already achieved. There are millions of citizens who, because of their physical conditions are prisoners in their homes because there isn’t any elevator or any elevator maintenance. FIABA project aims at implementing “a Space for all” or “a landscape for all” following the path of the ONU Convention on the Rights of People with disabilities with an emphasis on architectural, cultural, and psychological barriers, the last ones in particular, create barriers to equal opportunities and they are often carriers of discrimination. The principle of accessibility is invoked in Article 9 of the Convention which confirms the principle that people have a right to live independently and participate fully in all spheres of life and thus States are required to take all necessary measures to ensure accessibility to physical environment, transport, information and communications, including systems and technologies of information and communication and other facilities and services open to the public, both in urban and rural areas.